Peran Suku Bunga Sebagai Variabel Moderasi: Return On Asset, Debt To Equity Ratio, Current Ratio Terhadap Return Saham Pada Perusahaan Food Beverage yang Terdaftar di BEI 2019-2023 - Yeni, Fitri; Nola, Silvia; Edriani, Devi; Putri, Nabila Ulfa Maharani (Universitas Negeri Padang, 2024)
Food and beverage companies are considered attractive investment opportunities due to their extensive use across various societal sectors and their potential to generate substantial returns on invested capital. This study aims to investigate the impact of return on assets (ROA), debt-to-equity ratio (DER), and current ratio (CR) on the stock returns of food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Additionally, it examines how interest rates might moderate the relationship between these financial ratios and stock returns. The research relies on secondary data from the financial statements of these companies during the specified period. A purposive sampling method was employed to select 26 companies from an initial population of 29. The data analysis techniques include panel data regression, classical assumption testing, and multiple regression analysis (MRA) using Eviews 12. The findings reveal that ROA, DER, and CR significantly affect stock returns. Furthermore, the study demonstrates that the interactions between ROA, DER, CR, and stock returns in the food and beverage sector are significantly influenced by changes in interest rates.